Father's Role in Shaping Character of Responsibility in Early Childhood - Rustiana, R; Asmawulan, Tri (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This study explores how fathers’ involvement in early childhood care influences the development of responsibility character in young children. By focusing not only on the frequency of paternal presence but also on the quality of father–child interactions, it seeks to fill gaps in existing research that often overlooks contextual factors such as work demands and family structure. Methodology: Employing a qualitative design, the research collected data through in‑depth interviews and naturalistic observations of children and their fathers, deliberately sampling families with varying levels of paternal engagement. Thematic analysis was used to identify recurring patterns in fatherly involvement and to trace how these patterns relate to young children’s emerging sense of responsibility. Results: Findings reveal that limited father involvement—often driven by busy work schedules or complex family circumstances— negatively impacts children’s acquisition of responsibility traits. In contrast, fathers who consistently engage in high‑quality interactions—such as shared problem‑solving, age‑appropriate chores, and guided reflection on actions—foster stronger responsibility in their children. Applications/Originality/Value: By highlighting the critical role of consistent, meaningful paternal engagement, this study provides actionable insights for parenting programs, early‑childhood educators, and policymakers aiming to support character development. Its context‑sensitive approach underscores the need for workplace policies and community resources that enable fathers to participate more fully in early childcare, ultimately promoting the growth of independent and responsible individuals.